Knowledge, attitudes, behaviours, and beliefs of healthcare provider students regarding mandatory influenza vaccination - Heba Ghandora; Donna M. Halperin; Jennifer E. Isenor; Beth A. Taylor; Philippe Fullsack; Antonia M. Di Castri; Scott A. Halperin (Taylor & Francis Group, 2019)
Influenza infection poses the same risk to healthcare students as to practising clinicians. While there is substantial dialog about the benefits, risks, and ethics of mandatory influenza immunization policies in Canada, there has been little engagement of healthcare students. To explore the knowledge, attitudes, beliefs, and behaviours of healthcare students, we administered a web-based survey to students at Dalhousie University. Influenza vaccination status varied by program type, with 86.3% of medical students (n = 124) and 52.4% of nursing students (n = 96) self-reporting receipt of the influenza vaccine both in the previous and current seasons; pharmacy students' coverage fell between the two. Pharmacy students had higher mean knowledge scores (10.0 out of 13 questions) than medical (9.26) and nursing (8.88) students. Between 56.1% and 64.5% of students across disciplines were in support of a mandatory masking or vaccination policy, and between 72.6% and 82.3% of students would comply if such a policy were in place. A sense of duty to be immunized, desire to be taught more about influenza and influenza vaccine, belief that the hospital has a right to know vaccination status, support for declination policy, and willingness to accept consequences of noncompliance were all predictors of student support of mandatory policies. Medical and pharmacy students tended to hold more pro-influenza vaccination attitudes, had higher knowledge scores, and better vaccine coverage than nursing students. Based on the overall vaccination behaviour, knowledge, beliefs, and attitudes of students surveyed, this study demonstrates that mandatory influenza immunization policies are generally supported by the next generation of practitioners.